INTERCHANGE NODES IN SELECTED CITIES (Perner's Contacts, 2011)
This paper deals with the issue of localization of public transport interchange nodes in three selected cities in the Czech Republic – Prague, Brno and Ostrava. The main motive is to refine the results of the database of transport connections, which is preparing for the needs of the Integrated Information Portal of the Ministry of Labour and Social Affairs as the part of the project Implementation of Tools for Spatial Analysis of Labour Market Activity of Labour Offices supported by the Ministry of Labour and Social Affairs. The current solution has been replaced by the new approach when particular cities are defined by a set of public transport stops – interchange nodes – the stops often used for change between urban and public transport for the commuting at the beginning of shifts (at 6, 7, 8, 14 and 22 o‘clock). Overall 61 transport interchange nodes have been located in these three cities. Transport service areas around these three cities have been created and compared based on the methodology of defining the representing stops within these cities – any stop representing the city or any of interchange nodes. The results provide significant improvement of results and proved more accurate results than the current solution
Keywords: interchange node; urban transport; public transport; commuting